PENGARUH INTELLECTUAL CAPITAL, CORPORATE SOCIAL RESPONSIBILITY, DAN SALES GROWTH TERHADAP FIRM VALUE - Ferry Adang (Jurnal Bina Akuntansi, 2019)
This research has a purpose of obtaining empirical evidence regarding the effect of intellectual capital, corporate social responsibility, and sales growth on firm value of the manufacturing companies listed in the Indonesia Stock Exchange (IDX) in 2014 – 2016 period. The research conducted by obtaining 93 samples using purposive sampling method. The result of this research show that the independent variables have effects on firm value (Tobin’s Q) simultaneously (F test). The t test result showed that intellectual capital (VAIC) has a significant positive effect on firm value while the others have no significant effect on firm value